Analysis Approaches to Identify Pharmacogenetic Associations With Pharmacodynamics. Issue 3 (28th June 2021) - Hertz, Daniel L.; Ramsey, Laura B.; Gopalakrishnan, Mathangi; Leeder, J. Steven; Van Driest, Sara L.
Abstract : Pharmacogenetics (PGx) seeks to enable selection of the right dose of the right drug for each patient to optimize therapeutic outcomes. Most PGx focuses on pharmacokinetics (PKs), due to our relatively advanced understanding of the genes involved in PKs and the causative effects of variants in those genes. Genetic variants can also affect pharmacodynamics (PDs), but relatively few PGx‐PD associations have been identified. This is partially due to a more limited understanding of the relevant genes and the consequences of genetic variation, but is also due in part to the potential confounding of PK variability in assessments of clinical outcomes that have a contribution from both PKs and PDs. For example, it is challenging to confirm the effect of mu opioid receptor (OPRM1) genetic variation on opioid response due to the contribution of CYP2D6 genotype to bioactivation of some opioid drugs (i.e., codeine and tramadol). The objectives of this mini‐review are to describe several recent efforts to discover and validate PGx‐PD that disentangle the influence of PK variability and propose potential approaches that could be used in future PGx‐PD analyses. We use the effect of OPRM1 genetics on opioid response to illustrate how these analyses could be conducted and conclude by discussing how PGx‐PD could be translated into clinical practice to improve therapeutic outcomes.